Management of a Complex Supracondylar Periprosthetic Femur Fracture with Intramedullary Strut Allograft and Bilateral Locking Plates. (17th November 2021) - Moukarzel, Rita; Aouad, Dany; Daher, Mohammad; Ghanem, Wendy; Ezzeddine, Hady; El Rassi, George
Abstract : Supracondylar periprosthetic femoral fractures occurring above total knee replacements have been considered a rare entity. However, they continue to increase in frequency with the increasing number of arthroplasties and the improvement in morbidity and mortality in the concerned patient population. The management of periprosthetic distal femoral fractures is a challenging orthopedic problem. In this brief communication, a case of 49-year-old woman with rheumatoid arthritis who sustained a low distal comminuted periprosthetic femoral fracture is presented. Her fracture was eventually managed with an intramedullary fibular strut allograft and bilateral locking plate placement reaching satisfactory healing and restoration of alignment. The primary aim of this report is to provide insight into this novel technique as a successful alternative to other standard surgical options.